VD_FINDINFO HC / 2015 / 308 vom 13. März 2015 - VD Tribunal cantonal (2015)
HYPOTHÈQUE LÉGALE DES ARTISANS ET ENTREPRENEURS, REJET DE LA DEMANDE, RETARD | 839 al. 2 CC, 961 al. 3 CC, 308 al. 1 let. b CPC (CH)